Classical mechanics of particles and rigid bodies - Gupta, Kiran C. (New Delhi: New Age International, 1997)
This book provides a comprehensive coverage of all the diverse topics in Classical Mechanics, and is designed to serve as a textbook for graduate students of Physics and as a workbook for Engineering students. It includes the often-neglected topics of relativistic scattering, non-linear oscillatory systems, canonical perturbation theory and vibrations of continuous systems. A special feature of this book is the inclusion of more than two hundred examples and worked problems. The second edition is thoroughly revised in particular the chapters on Special Theory of Relativity and Relativistic Mechanics are rewritten with the metric (1, -1, -1, -1).
Appendix 644-658p.; Index 659-667p.
Keywords: Classical mechanics; Mechanics; General Science